ANCIENT EARTHQUAKES AND VOLCANIC ERUPTIONS IN THE ELBRUS REGION - Bogatikov O.A.; Gurbanov A.G.; Rogozhin E.A.; Marakhanov A.V.; Spiridonov A.V.; Shevchenko A.V.; Burkanov E.E. (My University, 2003)
New evidences of previously unknown Holocene catastrophic earthquakes in the Elbrus region, the northern Caucasus are reported. Ages of four seismic events over the recent 5500 years were determined by radiocarbon dating of paleoseismic dislocations. Their recurrence period was also estimated. The chronological comparison of ancient seismic shocks and volcanic eruptions showed that various manifestations of endogenic activity lack a direct correlation.